Answer:
There are no solutions.
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
2(9x−6)=6(3x−2)+2
(2)(9x)+(2)(−6)=(6)(3x)+(6)(−2)+2(Distribute)
18x+−12=18x+−12+2
18x−12=(18x)+(−12+2)(Combine Like Terms)
18x−12=18x+−10
18x−12=18x−10
Step 2: Subtract 18x from both sides.
18x−12−18x=18x−10−18x
−12=−10
Step 3: Add 12 to both sides.
−12+12=−10+12
0=2
Answer:
yes
Step-by-step explanation:
Answer:
35 is greater than the other options.Step-by-step explanation:
Answer:
1. c 2. c 3. b
Step-by-step explanation:
but im not sure